Modified Dalian Medical Stone for Removing Ammonium from Aquaculture Water - Fu, Kan; Yue, Ping; Li, Hui; Xia, Qibin; Li, Huijun (Asian Journal of Chemistry, 2012)
To improve the ammonium exchange capacity of the medical stone, its modifications in different solutions have been tested, respectively. The ammonium-exchange isotherms of the modified medical stone have been determined and compared. The renewable ammonium exchange capacity of the medical stone has been further studied. The results indicated that the ammonium exchange of medical stone increased as the average pore diameter and the BET surface area increased, after the medical stone were soaked with HCl and H2SO4 solutions. The modified method soaking with NaCl solution was superior to them, because the sodium content of this modified medical stone increased, leading to a more improved ammonium exchange capacity. The ammonium exchange capacity decreased with modified ion in the order Na+ > K+ > Mg2+ > Ca2+. When the ammonium concentration was 150 mg/L, the ammonium exchange capacity of medical stone modified with 98 ºC NaCl solution increased 80.4 %. For the ammonium exchange isotherms of medical stones, the Freundlich isotherm model yielded a much better fit than that of Langmuir isotherm model. After three times regeneration, the ammonium uptake of medical stone was changed little. Its exchange capacity was stable.